2014
DOI: 10.1016/j.jinteco.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and imperfect labor market sorting

Abstract: This paper focuses on the ability of the labor market to correctly match heterogeneous workers to jobs within a given industry and the role that globalization plays in that process. Using matched worker-firm data from Sweden, we find strong evidence that openness improves the matching between workers and firms in industries with greater comparative advantage. This suggests that there may be significant gains from globalization that have not been identified in the past -globalization may improve the efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Some authors acknowledge the possible bias but do not compute it (e.g. Card et al, 2013;Cornelißen & Hübler, 2011;Davidson et al, 2010;Graham et al, 2012;Sørensen & Vejlin, 2013). We therefore venture to evaluate the bias correction expressions without handling any large matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors acknowledge the possible bias but do not compute it (e.g. Card et al, 2013;Cornelißen & Hübler, 2011;Davidson et al, 2010;Graham et al, 2012;Sørensen & Vejlin, 2013). We therefore venture to evaluate the bias correction expressions without handling any large matrices.…”
Section: Introductionmentioning
confidence: 99%
“…7 Differences in the workforce composition are also in line with the models of, for example, Helpman et al (2010), Davidson et al (2008) or Yeaple (2005). Krishna et al (2011) and Davidson et al (2010) have also found empirical evidence for matching effects and sorting. In a similar context, Krishna et al (2011) have shown, for Brazil, that the impact of trade openness on wages becomes insignificant if match effects are simultaneously considered.…”
Section: Matched Employer-employee Data For Germanymentioning
confidence: 60%
“…Several studies have suggested that economic openness impacts prices and productivity (Alcala & Ciccone, 2004; Auer et al, 2013; Auer & Fischer, 2008). Improved labor market matching has been identified as an important mechanism in the link from openness to productivity (Davidson et al, 2014). In rich countries, trade‐induced changes to consumer prices typically favor the poor because they spend relatively more in trade‐intensive sectors (Fajgelbaum & Khandelwal, 2016).…”
Section: Theoretical Expectations and Related Literaturementioning
confidence: 99%